Isolation and characterization of a β-propeller gene containing phosphobacterium Bacillus subtilis strain KPS-11 for growth promotion of potato (Solanum tuberosum L.) - Hanif, Kashif; Hameed, Sohail; Imran, Asma; Naqqash, Tahir; Shahid, Muhammad; Van Elsas, Jan Dirk (Frontiers in Microbiology, 2015)
Phosphate-solubilizing and phytate-mineralizing bacteria collectively termed as phosphobacteria provide a sustainable approach for managing P-deficiency in agricultural soils by supplying inexpensive phosphate to plants. A phosphobacterium Bacillus subtilis strain KPS-11 (Genbank accession no. KP006655) was isolated from potato (Solanum tuberosum L.) rhizosphere and characterized for potato plant growth promoting potential. The strain utilized both Ca-phosphate and Na-phytate in vitro and produced 6.48 µg mL-1 indole-3-acetic acid in tryptophan supplemented medium. P-solubilization after 240 h was 66.4 µg mL-1 alongwith the production of 19.3 µg mL-1 gluconic acid and 5.3 µg mL-1 malic acid. The extracellular phytase activity was higher (4.3 x 10-10 kat mg-1 protein) than the cell-associated phytase activity (1.6 x 10-10 kat mg-1protein). B. subtilis strain KPS-11 utilized 40 carbon sources and showed resistance against 20 chemicals in GENIII micro-plate system demonstrating its metabolic potential. Phytase-encoding gene β-propeller (BPP) showed 92% amino acid similarity to BPP from B. subtilis (accession no.WP_014114128.1) and 83% structural similarity to BPP from B. subtilis (accession no 3AMR_A). Potato inoculation with B. subtilis strain KPS-11 increased the root/shoot length and root/shoot weight of potato as compared to non-inoculated control plants. Moreover, rifampicin-resistant derivative of KPS-11 were able to survive in the rhizosphere and on the roots of potato up to sixty days showing its colonization potential. The study indicates that B. subtilis strain KPS-11 can be a potential candidate for development of potato inoculum in P-deficient soils.